A Dragonfly Algorithm Application: Optimizing Solar Cell Single Diode Model Parameters. (January 2020) - Mat Isa, Zainuddin; Mohd Nayan, Norkharziana; Ashbahani Mohamad Kajaan, Nor; Hafiz Arshad, Mohd
Abstract: This paper provides an overview of optimizing solar cell single diode parameters using Dragonfly Algorithm. The 57 mm diameter commercial (R.T.C. France) silicon solar cell measurement data are taking as the data source for the optimization process. The results produced are compared with NM-PSO and IJAYA algorithms to observe the efficiency, accuracy and reliability of the proposed approach